2021
DOI: 10.3390/biomedicines9040395
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Cold-Inducible RNA-Binding Protein (CIRP) Promotes Angiogenesis and Regeneration of Ischemic Tissue by Inducing M2-Like Macrophage Polarization

Abstract: Cold-inducible RNA-binding protein (CIRP) is an intracellular RNA-chaperone and extracellular promoter of inflammation, which is increasingly expressed and released under conditions of hypoxia and cold stress. The functional relevance of CIRP for angiogenesis and regeneration of ischemic muscle tissue has never been investigated and is the topic of the present study. We investigated the role of CIRP employing CIRP deficient mice along with a hindlimb model of ischemia-induced angiogenesis. 1 and 7 days after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 117 publications
(181 reference statements)
3
16
0
Order By: Relevance
“…In anti-CIRP antibody-treated mice a predominance of the anti-inflammatory M2-like polarized macrophages at the ischemic muscle tissue site was observed, as compared to control mice (for an overview see Figure 6). Overall, the blockade of eCIRP enhanced angiogenesis in vivo, reminiscent of results obtained in CIRP-deficient mice [59], to indicate that eCIRP is mainly responsible for modulating angiogenesis. Figure 6.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In anti-CIRP antibody-treated mice a predominance of the anti-inflammatory M2-like polarized macrophages at the ischemic muscle tissue site was observed, as compared to control mice (for an overview see Figure 6). Overall, the blockade of eCIRP enhanced angiogenesis in vivo, reminiscent of results obtained in CIRP-deficient mice [59], to indicate that eCIRP is mainly responsible for modulating angiogenesis. Figure 6.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, we showed in a murine hindlimb model that the genetic ablation of CIRP (including eCIRP and iCIRP) improves angiogenesis and the regeneration of ischemic tissue damage, most likely through the predominance of regenerative anti-inflammatory M2like polarized macrophages and the reduced accumulation of neutrophils and NETs [59]. Whether these changes in leukocyte recruitment, macrophage polarization, and ameliorated angiogenesis are attributed to the lack of intra-or extracellular CIRP remains unclear so far.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this group already hypothesized that their findings might not be only restricted to the retinal. In our study on ischemic muscle tissue, we found in C3-deficient mice a reduced number of M1-like polarized macrophages but an increased number of M2-like polarized macrophages, which are well described for their pro-angiogenic function [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 94%
“…CIRP mainly regulates the transcription and processing of RNA in the nucleus, and the translation and transformation of mRNA in the cytoplasm ( Zhu et al, 2016 ; Zhong and Huang, 2017 ). CIRP participates in multiple cell physiological activities through its regulation of targets ( Xia et al, 2012 ), for example, cell survival, proliferation, circadian rhythm regulation, telomere maintenance, tumor formation and development ( Zhong and Huang, 2017 ; Indacochea et al, 2021 ; Kübler et al, 2021 ). CIRP expression has been detected in various tissues and cells, especially in mild hypothermia ( Liu et al, 2019 ), hypoxia ( Wellmann et al, 2004 ), UV radiation ( Sun et al, 2018 ), heat stress ( Nishiyama et al, 1998 ), endoplasmic reticulum stress ( Khan et al, 2017 ), and oxidative stress ( De Leeuw et al, 2007 ), where its expression is up-regulated and respond to a variety of stress conditions by changing its expression and regulating mRNA stability through its binding site on the 3′-UTR of its targeted mRNAs ( Zhong and Huang, 2017 ; Zhong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%